CFD Development for Multiphase Flows in HZDR - Putra, Ryan Anugrah; Lucas, Dirk (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Over the last 20 years, Helmholtz-Zentrum Dresden-Rossendorf (HZDR) has contributed in the development of Computational Fluid Dynamics (CFD) for multiphase flows. In the CFD department, a lot of efforts have been performed to provide CFD as a reliable simulation tool for the design, optimization and safety analyses of medium and large scale applications. The tool is expected to contribute in the improvement of the efficient use of energy and resources as well as safety operation. Most of the research activities are related to gas-liquid flows covering dispersed flows, stratified flows and mixture or transition flows. The development is carried out using Euler-Euler two or multi fluid model as the basis. The paper discussed some characteristics of the CFD model development in HZDR started with “simple”, reliable experimental data for validation and stepwise and continuous improvement. The examples of each characteristic were given. The discussions covered three CFD modeling frames which had been developed in HZDR; they were iMUSIG for dispersed flows, AIAD for stratified flows and GENTOP concept for mixture or transitional flows.